Seaweed and its antioxidant content at Batu Layar beach, Senggigi, West Lombok Regency - Nunik Cokrowati; Fisma Apriliyanti; Nuryatin Nuryatin; Jayusri Jayusri; Muhammad Junaidi; Yuliana Asri (Depik, 2024)
Seaweed is macro algae that it one of export commodity at Indonesia. In addition to having economic value, macroalgae also have an important role in aquatic ecosystems. macroalgae play a role as primary producers because of their ability to photosynthesize, produce organic matter, and oxygen in the aquatic environment. Waters on Lombok Island that are overgrown with seaweed include Batu Layar beach. Batu Layar sub-district is part of the tourism area located in the coastal area. Batu Layar sub-district includes a cultivation area consisting of a variety of land uses ranging from agriculture, livestock, fishing and so on. This study aimed to analyze the diversity of seaweed species in the coastal waters of Batulayar, Senggigi, West Lombok Regency along with antioxidant and chlorophyll-a content. The research was conducted in November 2023 in the waters of Batu Layar, Senggigi, West Lombok Regency. The research methods used in this study were survey methods and method explanation of antioxidant content and chlorophyll was carried out in the laboratory, by taking random samples based on the boundaries of the predetermined area as many as 4 stations. The result of this research are identified species of seaweed including Sargassum sp., Padina, Caulerpa, Galaxaura, Ulva, Gelidium, Acanthophora, Iaxaura, Halimeda, Boergesenia forbesii, Corallina, and Turbinaria. Padina antioxidant levels reached 81,31% and chlorophyll 14,35 mg/l. It can be concluded that there are 12 types of seaweed that grow wild consisting of four species each of green, brown, and red alga. Padina has the highest antioxidant content of 81,31%.Keywords:AquacultureAntioxidantChlorophyllSeaweedSargassum.